Removal of Lead Ion from Aqueous Solutions Using Sawdust Coated by Polyaniline - R. Ansari; F. Raofie (E-Journal of Chemistry)
Polyaniline was synthesized chemically, coated on sawdust via cast method in the form of emeraldine base (EB) from formic acid as solvent, and used as an adsorbent for removal of lead ion or from aqueous solution. The effects of some important chemical and physical factors in removal efficiency have also been investigated. Among the different parameters, the effect of pH was the most prominent. It was found that metal uptake is occurred under neutral or slightly alkaline conditions, while under relatively strong acidic media, the sorption of the investigated metal ions was negligible and desorption is a predominant process. It was found that undoped PANi (EB form) coated on polar substrates such as sawdust (SD) can be used as an effective adsorbent for removal of heavy metal ions in water and wastewater treatments. All the previous investigations and applications take advantage of the electrical conductivity (metallic), electrochemical (redox activity) and electrochromic properties of the polyaniline. While; in this research, we have taken advantage of the chelating properties of PANi for metal sorption.